ANALISIS PREFERENSI TERHADAP STRATEGI PENYEDIA JASA PENGIRIMAN UANG DALAM PEMBENTUKAN KOMITMEN TENAGA KERJA INDONESIA - Makhdum Asqar, Muhabbat; Purwoko, Bambang; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2016)
This study analyzes the effect of migrant workers on election preferences option remittance services, TKI preferences influence on the formation of commitment and analyze the commitment as a mediator variable between preferences and remittance options. The research methodology using quantitative descriptive approach. The analysis technique used in this research is Structural Equation Model (SEM). Data obtained running by using the software LISREL 8.70. The research concludes that there is a positive influence between the preference for the commitment and remittance options. Commitment does not significantly influence remittance options. Thus the variable no commitment can not be used as a mediator variable between preferences with the option money transfer services